Dense composite electrolyte hollow fibre membranes for high temperature CO2 separation - Zhuang, S.; Li, Y.; Zuo, M.; Tan, X.; Meng, B.; Yang, N.; Liu, Shaomin (Elsevier, 2014)
Inorganic membranes for high temperature CO2 separation has potential applications in clean energy delivery for CO2 capture. In this work, the gas tight oxygen ion conducting perovskite and carbonate composite electrolyte hollow fibre membranes were developed for CO2 separation at high temperatures. For this purpose, the La0.6Sr0.4Co0.2Fe0.8O3−α (LSCF) perovskite hollow fibre was firstly prepared as the porous support to impregnate and immobilize the carbonate phase. The composite electrolyte hollow fibre membranes were characterised by SEM, XRD, room-temperature gas leakage detection and CO2 permeation test at temperature regime from 500 to 900 °C. The maximum CO2 flux measured reached 1.0 mL cm−2 min−1 at 900 °C, which was improved by a factor up to 5 when compared with the previously developed membranes due to the much thinner separating layer achieved in the current membrane.